Discrete Geometry for Computer Imagery 17th IAPR International Conference, DGCI 2013, Seville, Spain, March 20-22, 2013, Proceedings - Gonzalez Diaz, Rocio; Jimenez, Maria Jose; Medrano, Belen Garfia (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2013)
This book constitutes the thoroughly refereed proceedings of the 17th International Conference on Discrete Geometry for Computer Imagery, DGCI 2013, held in Seville, Spain, in March 2013. The 34 revised full papers presented were carefully selected from 56 submissions and focus on geometric transforms, discrete and combinatorial tools for image segmentation and analysis, discrete and combinatorial topology, discrete shape representation, recognition and analysis, models for discrete geometry, morphological analysis and discrete tomography.